The new mercantilism : some problems in international trade, money and investment - Johnson, Harry G.; British Association for the Advancement of Science (Oxford, England : B. Blackwell, 1974)
The book is an organized related series of papers on policy issues around the main areas that Keynes himself dealt with, suitably modified for subsequent developments in the main subjects of policy concern.
Papers presented to Section F (Economics) at the 1973 Annual Meeting of the British Association for the Advancement of Science.
Includes bibliographical references and index.
rpm 02/11/2017
Loans
Keywords: International economic relations; International trade; International finance; Currency question